2020
DOI: 10.1051/0004-6361/202039128
|View full text |Cite
|
Sign up to set email alerts
|

Different sodium enhancements among multiple populations of Milky Way globular clusters

Abstract: We searched for clues to understand the different Na abundances measured in first and second generation stars of ancient Milky Way globular clusters. For that purpose, from the recent literature, we gathered the aforementioned Na abundances, orbital parameters, and structural and internal dynamical properties and ages in a homogeneous scale of 28 globular clusters. We found that the intra-cluster Na enrichment, which is measured by the difference of Na abundances between first and second generation stars, exhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Such a cluster origin agrees well with the cluster age (13.97±0.50 Gyr; Valcin et al 2020), its low metal-content ([Fe/H] = -1.99 dex; Marino et al 2019), and the difference in sodium abundance between first and second generation stars. Indeed, Piatti (2020) found that globular clusters with sodium abundance enrichments larger than 0.3 dex hinted at an accreted origin, particularly the oldest globular clusters. NGC 6809 has a sodium abundance enrichment of 0.72 dex (Piatti 2020).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a cluster origin agrees well with the cluster age (13.97±0.50 Gyr; Valcin et al 2020), its low metal-content ([Fe/H] = -1.99 dex; Marino et al 2019), and the difference in sodium abundance between first and second generation stars. Indeed, Piatti (2020) found that globular clusters with sodium abundance enrichments larger than 0.3 dex hinted at an accreted origin, particularly the oldest globular clusters. NGC 6809 has a sodium abundance enrichment of 0.72 dex (Piatti 2020).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Indeed, Piatti (2020) found that globular clusters with sodium abundance enrichments larger than 0.3 dex hinted at an accreted origin, particularly the oldest globular clusters. NGC 6809 has a sodium abundance enrichment of 0.72 dex (Piatti 2020).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Star clusters have long been extolled as critical test beds of stellar evolution while simultaneously serving as well-defined, individual data points for probing the temporal, chemical, and spatial evolution of the Galaxy owing to the unique distance, age, and chemical composition common to all stars within a cluster (see, e.g., Twarog et al 1997;Friel et al 2002;Netopil et al 2016;Donor et al 2020). While the claim of uniformity for the last two parameters has been successfully challenged by globular clusters exhibiting multigenerational abundance trends (see, e.g., Gratton et al 2004;Carretta et al 2009;Milone et al 2012;Piatti 2020), open clusters still retain the mantle of single-generation parametric homogeneity, apart from abundance variations due to the internal evolution of specific elements like Li or CNO. In particular, in the case of M67, diffusion and rotational mixing have arisen as potential sources of significant multielemental variations with evolutionary phase (Souto et al 2019;Boesgaard et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While the claim of uniformity for the latter two parameters has been successfully challenged by globular clusters exhibiting multigenerational abundance trends (see, e.g. Gratton, Sneden, & Carretta (2004); Carretta et al (2009); Milone et al (2012); Piatti (2020)), open clusters still retain the mantle of single-generation parametric homogene-ity, apart from abundance variations due to the internal evolution of specific elements like Li or CNO. In particular, in the case of M67, diffusion and rotational mixing have arisen as a potential sources of significant multi-elemental variations with evolutionary phase (Souto et al 2019;Boesgaard, Lum, & Deliyannis 2020).…”
Section: Introductionmentioning
confidence: 99%